Análisis de ítems y fiabilidad de una escala de disposición para el estudio en estudiantes de posgrado - Gorbalán Rojas, Rolylith Sutsé (2021)
The research aimed to analyze the items and reliability of a readiness scale for the study. The methodology that was used was the instrumental one under the classic theory of the tests, the homogeneity analysis was carried out and the internal consistency was analyzed by Cronbach’s Alpha.